Epidemiological Characteristics of Meningococcal Infection in Moscow - M. I. Gritsay; M. A. Koroleva; N. N. Fomkina; I. S. Koroleva (Эпидемиология и вакцинопрофилактика, 2020)
Aims. The purpose of this study was to identify current epidemiological features of meningococcal infection in Moscow.Materials and methods. Cases of invasive meningococcal disease in Moscow from 2014 to 2018 and the biomaterial from patients with an invasive meningococcal disease were analyzed.Results. The features of the epidemic process of meningococcal disease in Moscow were revealed: increasing in the incidence rate involving teenagers and young adults into the epidemic process; meningococcal strains of serogroups W and A increased in the etiology of the invasive meningococcal disease; high mortality rate.Conclusions. It seems reasonable to recommend vaccination against meningococcal disease by including adolescents, young adults and persons over 65 years old.